Reaver (2019), volume 1 ebook Hell's half-dozen. - Jordan, Justin (Reaver (2019), 2020)
Deep within the untamed continent of Madaras, a darkness builds that must be stopped at all costs. To prevent the end of this new world, the Imperials assemble six of their most despicable prisoners—a turncoat, a skin eater, a sorcerer, his bodyguard, a serial killer, and the Devil’s Son. They are Hell’s Half-Dozen. JUSTIN JORDAN (LUTHER STRODE) and REBEKAH ISAACS (Buffy the Vampire Slayer) create a grim fantasy comic for a post-Game of Thrones world. Collects REAVER #1-6. Author: Justin Jordan. Illustrator: Rebekah Isaacs, Alex Guimarães. 2020 Skybound, LLC..